2018
DOI: 10.2217/pgs-2018-0147
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics to Prevent Heparin-Induced Thrombocytopenia: what do we know?

Abstract: Heparin-induced thrombocytopenia (HIT) is a life-threatening, immune-mediated adverse reaction to heparin anticoagulants. The inability to predict HIT represents a considerable liability associated with heparin administration. Genetic studies of HIT are challenging due to the scarcity of true HIT cases, potential for misclassification, and many environmental risk factors.Genetic studies have not consistently identified risk alleles for HIT, the production of platelet factor 4 (PF4)/heparin antibodies, nor the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Our patient had several risk factors for HIT including unfractionated heparin use, duration of treatment, therapeutic dosing, and increased age [2,13]. This patient's platelets rose from 63 to 85 after the heparin was initially stopped for 3 days but dropped to 60 following re-initiation of heparin.…”
Section: Discussionmentioning
confidence: 98%
“…Our patient had several risk factors for HIT including unfractionated heparin use, duration of treatment, therapeutic dosing, and increased age [2,13]. This patient's platelets rose from 63 to 85 after the heparin was initially stopped for 3 days but dropped to 60 following re-initiation of heparin.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported that 20%–30% of the inter-individual differences in drug metabolism and drug response were estimated to be due to genetic variations 35 , 36 . Until now, no pharmacogenomic studies related to heparin therapy have been conducted, except for heparin-induced thrombocytopenia 37 39 . Including genetic factors could improve the prediction of interindividual variabilities and will be the next step to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the FcγRIIa receptor have been shown to be associated with both HIT and HITT (Karnes 2018). The polymorphism H131R in the IgG binding region of FcγRIIa receptor has been associated with HIT in several populations, but a meta-analysis showed no difference in HIT between the wild-type and 131R variant (Trikalinos et al, 2001).…”
Section: Platelets (Megakaryocytes)mentioning
confidence: 99%
“…These PF4/heparin antibodies then engage with platelets, leading to platelet activation and ultimately thrombocytopenia. Despite extensive research efforts towards understanding the immunopathology of HIT, fundamental knowledge gaps persist regarding HIT etiology (Cuker 2011;Greinacher et al, 2011;Karnes 2018). The HIT immunogen, the roles of antigen presenting cells and T-cells, and the B cell subtypes that produce the antibody remain unknown (Arepally 2017).…”
Section: Introductionmentioning
confidence: 99%